ISOLATION OF CLOVE ESSENTIAL OIL BY FERMENTATION PROCESS - Khurotul Ainiyah; Fita Andriyani; Soemargono Soemargono; Nove Kartika Erliyanti (Konversi, 2021)
Clove essential oil is processed product of clove leaves which is used as perfumes and medicines. In general, the method used to extract clove leaf essential oil is the steam distillation method. This method has not maximized the yield essential oils produced because a lot of essential oils are still trapped in plant tissues. Modification of the essential oil isolation methods to produce more yields needs to be done, one of which is the fermentation method with the help Rhizopus oligosporus before the distillation process is carried out. The fermentation method is able to destroy the oil tissues on the leaves using enzymes produced by rhizopus oligosporus. The aims of this study were to isolate the essential oil clove leaves and look for the effect of the mass and fermentation time on the yield and content of clove leaf essential oil compounds produced. The results showed that the isolation  essential oils using fermentation methods was successfully carried out, the mass and fermentation time had a significant influence on the yield and content of essential oil chemical compounds. The best result was obtained at a mass of 35 grams with a fermentation time of 36 hours with a yield 0.32% and the content eugenol, caryopillene compounds obtained respectively at 93.43% and 2.28%.